Gene expression of ING4 gene in pancreatic cancers and splice forms of ING4 gene - Yıldırım, ć°brahim Halil; í‡akmak, Ecir Ali; Camcı, Celaleddin (Cellular and Molecular Biology, 2018)
Pancreatic cancer is characterized by rapid metastasis and resistant to medical treatments. As the other cancers, mutations of tumor suppressor genes that involved in suppression of cell growth are observed in pancreatic cancers. ING4 protein is one of the proteins involved in the regulation of p53 tumor suppressor gene functions. ING4 involved in suppression of cell proliferation, chromosome rearrangement, cell migration, and angiogenesis. In this study, gene expressions and splicing variants of ING4 gene were investigated. Fresh tumor and normal specimens of the same pancreatic cancer patients were used. Gene expression study carried out by calculating the brightness of the bands on agarose gel and splicing variants were detected by direct sequencing. According to the results, three splice forms of ING4 and a decrease in gene expression of ING4 were determined. Splicing type of ING4 affects the translocation of ING4 proteins into the nucleus. To determine the gene expression of each splicing variant, will further clarify the role of ING4 in pancreatic cancers.